Implementasi Cooperative Learning Pada Mata Pelajaran Al-Qur’an Hadist dalam Tinjauan Pembelajaran Abad 21 di MTs Salafiyah Tuban - Rahmawati, Endris; Huda, Mualimul (Education Mind Based Development Association, 2023)
Several problems related to PAI learning in Indonesia are due to students' lack of confidence in asking questions; they are only passive and often silent in learning. This problem also comes from educators, who still focus on understanding the material without paying attention to the right strategy. This teaching and learning process still leads to cognitive aspects, such as approach teacher-centred or just talking. The purpose of carrying out this research is to understand the forms, supporting and inhibiting factors that educators face and to know the implications of implementing cooperative learning on Al-Qur'an Hadith-based subjectsSkills 21st century learning at MTs Salafiyah Jatirogo Tuban. This type of research study is descriptive qualitative. The results of this study prove that the form's implementation of cooperative learning in the Al-Qur'an Hadith subject at MTs Salafiyah Asy Syafi'iyah Jatirogo Tuban using the typeTeams Games Tournament, Numbered Head Together, jigsaw, and group discussion. There are three steps in implementing cooperative learning: planning, implementation and evaluation. Supporting factors in successful cooperative learning include the role of the principal, who is open to teacher innovation, enthusiastic students, and the willingness of teachers to develop their competencies. At the same time, the inhibiting factors that become obstacles are the lack of time allocation, inadequate teaching aids and media, and students who look ordinary so that they are less conducive to learning. There are implications of implementing cooperative learning, namely facilitating students in understanding the material, practising responsibility and tolerance, increasing friendships, increasing the courage of students in asking questions and communicating with teachers and friends and so on.